Software engineering - Sommerville, Ian (Pearson Education, 2016)
This text seeks to lay out the fundamental concepts of this huge and continually growing subject area in a clear and comprehensive manner. The Tenth Edition contains new information that highlights various technological updates of recent years, providing readers with highly relevant and current information. The text strives to teach the innovators of tomorrow how to create software that will make our world a better, safer, and more advanced place to live.